The Problematic Jurisprudence on the Law of Defilement of Adolescents in Kenya (Strathmore Law Review, 2019)
The intention of the drafters of the 2006 Sexual Offences Act of Kenya was to curb the growing number of sexual crimes. The application of Section 8 of the Act by courts of law has, encountered some challenges, however, especially where adolescents are involved. Key among them is the identification of a victim where there is mutual defilement by children; the interpretation of Section 8(5) and (6) which provides a defence where the said child acted as an adult; the unjust outcomes of the mandatory minimum sentences in the Act; and the potential hindrance to the right to access reproductive health by adolescents. Therefore, this study seeks to provide solutions in dealing with these challenges. It advances the position that in certain instances, adolescents may consent to sexual intercourse, and so, stiff criminal sanctions may seem unwarranted. This study will rely on multidisciplinary studies such as medicine, in addition to the law, to further this argument. It proposes certain legislative reforms in order to avoid injustices while maintaining the legitimate interests of society to protect minors from sexual molestation.